2010
DOI: 10.1007/s10552-010-9539-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in relationship to different indicators of adult socioeconomic position in Turin, Italy

Abstract: Different socioeconomic indicators pinpoint to a series of specific risk factors that are related to specific phases of the life course. Individual level data, rather than ecological data, is preferred to accurately monitor social inequalities in cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 32 publications
7
53
1
3
Order By: Relevance
“…Our findings on the inter-relationship between area deprivation and education show the synergistic effect of area and individual SES measured by education and are consistent with others focusing on cancer [22] and lung function [40]. Consistent with others we too found, low education level and high deprivation was associated with increased lung and UADT cancer risk in males and the risk order implied greater influence of education [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings on the inter-relationship between area deprivation and education show the synergistic effect of area and individual SES measured by education and are consistent with others focusing on cancer [22] and lung function [40]. Consistent with others we too found, low education level and high deprivation was associated with increased lung and UADT cancer risk in males and the risk order implied greater influence of education [22].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with others we too found, low education level and high deprivation was associated with increased lung and UADT cancer risk in males and the risk order implied greater influence of education [22]. For females, being educated to some extent mitigated the effects of living in a deprived area; likewise living in an affluent area mitigated the effect of no education.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…At the same time, testis cancer is much more common in developed contest, thus the second men factor loading can be interpreted as a "social" factor, and positively associated with cancer more present in lower socioeconomic group, assuming higher values in poorer regions. Many studies conducted in all Western countries have reported large social inequalities in health, using a variety of socioeconomic indicators and including both general health and disease-specific outcomes (Spadea et al 2010).…”
Section: Resultsmentioning
confidence: 99%